Monitoring of injection moulding of thermoplastics - Speranza, Vito (Strojniški vestnik, 2013)
In this work, a series of injection moulding tests were conducted using a general purpose PolyStyrene, PS, and changing the holding pressure,injection temperature and cavity dimensions. The pressures at the interface with the mould at several positions along the flow-path weremeasured by means of pressure-temperature transducers. The samples were measured after moulding to determine dimensional accuracy,which was taken to be the target quality parameter. The pressure profiles obtained were then analysed using a recently developed procedurethat is able to estimate the local solidification history from pressure measurements. The local average solidification pressure, namely theaverage along the thickness direction of the pressures at which each layer solidifies, could thus be estimated. This parameter is known tocorrelate well with shrinkage and thus a master-curve can be created that can be adopted to monitor the quality of the moulded part on line.
Keywords: brizganje; čas strjevanja; injection moulding; kontrola kakovosti; krčenje; povprečni tlak strjevanja; predelava polimerov; quality control; shrinkage; strjevanje; tlak v gnezdu